P‐25: OLED Displays with a Specialized Pixel Circuit for Automotive Applications. Issue 1 (30th May 2018) - Nonaka, Yoshihiro; Yanase, Jiro; Shimoda, Masamichi; Matsueda, Youichiro; Mori, Shigeru; Tanabe, Hiroshi; Shigemura, Koji
Abstract : A 4.2 inch. OLED display which shows high luminance of peak‐white over 800 cd/m 2 has been developed for automotive application. A specialized pixel circuit is proposed to drive OLEDs by current range over 1 µA and reset OLEDs within one frame.